Eating Out is Associated with Self-Reported Food Poisoning: a Western Australia Population Perspective, 1998 to 2009 - Pollard, Christina; Meng, Xingqiong; Williamson, S.; Dodds, J.; Binns, Colin (Cambridge University Press, 2013)
OBJECTIVE: To explore factors associated with self-reported food poisoning among Western Australian adults between 1998 and 2009.DESIGN: Data were pooled from four Nutrition Monitoring Surveys Series which included information on suspected food poisoning among Western Australian adults. Descriptive statistics and multinomial regression analyses were used to describe factors associated with self-reported food poisoning, food safety knowledge and behaviours.SETTING: Population of Western Australia estimated to be 2•5 million in 2009. SUBJECTS: A representative sample of 4494 adults aged between 18 and 64 years.RESULTS: There was no significant change in self-reported food poisoning over time, with about 18 % saying they had suspected food poisoning in the last 6 months. Overall, 2•1 % said they had confirmed their food-borne illness with a nurse of doctor. People less than 34 years old, those with a university degree and people who ate meals out on the day prior to the survey (one meal: OR = 1•30, 95 % CI 1•04, 1•62; two meals: OR = 2•21, 95 % CI 1•30, 3•76) were the most likely to report food poisoning. Younger people were also more likely to have their food poisoning confirmed by a health professional. Use of refrigerator thermometers and cool bags for storing food increased significantly between 2004 and 2009.CONCLUSIONS: Findings support the inclusion of food safety advice in dietary recommendations. Food safety and handling education and training is recommended for food businesses, particularly the takeaway food sector, and for consumers. Because food poisoning is reported more often by younger people, food safety education should begin during childhood.